DETERMINAN KETAHANAN MODAL BANK SYARIAH DI INDONESIA: PENDEKATAN ECM - Wilara, Giras Risti; Basuki, Agus Tri (Jurnal Ekonomi & Studi Pembangunan, 2016)
This research aims to analyze the impact of Return on Assets (ROA), Financing to Deposit Ratio (FDR), Operational Expense to Operational Income (BOPO), and inflation on Capital Adequacy Ratio (CAR) in both short and long term. The object of this research is Shari’ah Banks in Indonesia by gaining the data from January 2013 to June 2015 from information published by some institutions such as Financial Services Authority (OJK) and Central Bureau of Statistics (BPS). The data were analyzed by Error Correction Model (ECM) method. Based on the analysis, the result shows that ROA and Inflation have positive and significant influence toward CAR, FDR has positive and negative influence toward CAR, whereas BOPO has no influence toward CAR. Besides, there is a short term and long term relationship between ROA, FDR, and inflation toward CAR.